Determinants of Manufacturing Company Tax Avoidance Listed on the Indonesia Stock Exchange 2015-2020 - Darmansyah Darmansyah; Bambang Purwoko; Tri Widyastuti (eCo-Buss, 2022)
The practice of tax avoidance cannot be avoided as long as the tax regulations are still multi-interpreted. Companies take advantage of it from the financial and non-financial aspects. The research focuses on financial aspects, such as return on assets, debt to equity ratio, firm size, sales growth, current ratio and capital intensity. The object of the research is manufacturing companies listed on the Indonesia stock exchange for the period 2015 to 2020. Sampling uses the purposive sampling method. The sample used in this study was 545 test units, consisting of 91 companies for 6 years of research using moderated regression analysis. The results of data processing obtained the following results: return on assets, debt to equity ratio, firm size, sales growth and capital intensity have an influence on tax avoidance. While the current ratio has no effect on tax avoidance